2018
DOI: 10.1109/jbhi.2017.2765639
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Approaches Toward Assessing the Risk of Developing Cardiovascular Disease as a Long-Term Diabetes Complication

Abstract: The estimation of long-term diabetes complications risk is essential in the process of medical decision making. Guidelines for the management of Type 2 Diabetes Mellitus (T2DM) advocate calculating the Cardiovascular Disease (CVD) risk to initiate appropriate treatment. The objective of this study is to investigate the use of sophisticated machine learning techniques toward the development of personalized models able to predict the risk of fatal or nonfatal CVD incidence in T2DM patients. The important challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
2
47
0
2
Order By: Relevance
“…The figure below illustrates the five approaches for feature selection. Algorithms 2015 -2019 ANN [8], [19], [2], [20], [21],[11] K-means [22] Logistic [22], [9], [2], [20], [23], [24], [11] Decision Tree [1], [20], [3], [25], [24], [10], [26] SVM [27], [2], [1], [20], [3], [21],[24] KNN [1], [21], [24] Random Forest [1], [24] Naive Bayes [3], [23], [25], [24] Designed algorithms [28], [13], [5], [29], [9] Table 1: Shows the trends of used algorithms in previous literature.…”
Section: Feature Selectionmentioning
confidence: 99%
“…The figure below illustrates the five approaches for feature selection. Algorithms 2015 -2019 ANN [8], [19], [2], [20], [21],[11] K-means [22] Logistic [22], [9], [2], [20], [23], [24], [11] Decision Tree [1], [20], [3], [25], [24], [10], [26] SVM [27], [2], [1], [20], [3], [21],[24] KNN [1], [21], [24] Random Forest [1], [24] Naive Bayes [3], [23], [25], [24] Designed algorithms [28], [13], [5], [29], [9] Table 1: Shows the trends of used algorithms in previous literature.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Data collected from a 5-year follow up of 560 T2DM patients at the Hippokration General Hospital of Athens, including 41 patients (7.32%) with CVD incidents during their follow-up period, were used for development and evaluation purposes [15]. Out of the 41 patients, four patients experienced stroke and the rest experienced CHD.…”
Section: Datasetmentioning
confidence: 99%
“…In order to avoid over-fitting, an ensemble learning method, based on a sub-sampling approach, was applied towards the generation of appropriate training subsets from the original data. Multiple individual models were trained on these subsets and combined to produce the final CVD risk scores [15]. In particular, the initial training dataset was divided into positive (for CVD) and negative (for CVD) instances.…”
Section: A Ensemble Learning Scheme 1) Sub-sampling Approachmentioning
confidence: 99%
“…In recent years, with ever-growing data from hospitals, there are great benefits of employing machine learning technology to provide insights, augment prevention, and reduce costs in healthcare settings. Multiple machine learning models have been applied for producing the risk of developing complications in diabetic patients (Zarkogianni et al, 2018 ). Nowak et al developed a cardiovascular risk prediction system using gradient-boosted machine learning and lasso regularized Cox regression and revealed that multiprotein arrays could be useful in identifying individuals with T2DM who were at the highest risk of CVD (Nowak et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%